2009
DOI: 10.1002/chem.200900329
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Orthogonal Functionalization of [60]Fullerene e,e,e‐Trisadducts with Two Spherically Defined Addend Zones

Abstract: e,e,e-Trisadducts 13 and 15 have been prepared by a highly regioselective threefold cyclopropanation of tripodal malonates 10 and 12 with C60. The yield and regioselectivity depend on the length and structure of the tethers that connect the malonate units to the focal benzene core of 13-15. As a consequence of the template-directed synthesis, all e,e,e-trisadducts were formed as in/out isomers exclusively and contain two spherically well-defined addend zones with equatorial and polar orientation, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 60 publications
(61 reference statements)
1
21
0
Order By: Relevance
“…After purification by column chromatography, the product was determined to be trisbromo derivative 12 by mass spectrometric and NMR spectroscopic analysis. The same compound had been generated previously from the corresponding benzene templated trisadduct, demonstrated by spectroscopic data 10b. Additional experiments showed that neither TMSBr, nor DBU alone caused deprotection.…”
Section: Resultsmentioning
confidence: 62%
“…After purification by column chromatography, the product was determined to be trisbromo derivative 12 by mass spectrometric and NMR spectroscopic analysis. The same compound had been generated previously from the corresponding benzene templated trisadduct, demonstrated by spectroscopic data 10b. Additional experiments showed that neither TMSBr, nor DBU alone caused deprotection.…”
Section: Resultsmentioning
confidence: 62%
“…[19] Racemic, C 3 -symmetrical adducts of C 60 with the inherently chiral e,e,e addition pattern were obtained by Hirsch and co-workers through addition of achiral tripodal conjugates having trimalonates linked to a benzene-1,3,5-trimethylene or a benzene-1,3,5-trioxy core. [28,29] Addition of the macromonocycle tris(octamethylene) cyclotrimalonate to C 60 provided the C 3 -symmetrical e,e,e tris-adduct in high yields, and the achiral C 3v -symmetrical trans-4,trans-4,trans-4 derivative as a minor product. [30] A chiral cyclotrimalonate with enantiomerically pure spacer units derived from -mannitol afforded C 3 -symmetrical adducts in a 4:1 ratio as separable diastereoisomers with enantiomeric e,e,e fullerene addition patterns.…”
Section: Introductionmentioning
confidence: 99%
“…The tether-directed remote functionalization method has been successfully applied for the synthesis of C 3 -symmetrical trisadducts of C 60 by the groups of Diederich, 6 Hirsch, [7][8][9][10][11][12] Nierengarten 13-15 and ours. [16][17][18] Opened-and closed-structure tethers equipped with three malonate groups were utilized for this purpose and all possible C 3 -symmetrical addition patterns have been accessed except the cis-1,cis-1,cis-1 (all-cis-1) which is not energetically favored owing to the steric hindrance of the addends.…”
Section: Methodsmentioning
confidence: 99%
“…The reports of Hirsch [9][10][11][12] and Nierengarten 13,14 on the synthesis of e,e,e trisadducts of C 60 with tripodal tethers equipped with malonate moieties, prompted us to design opened-structure tether 10 bearing ortho-quinodimethane precursors covalently connected to the phloroglucinol focal point via two-carbon alkyl chains (Scheme 3). Bromoethanol was firstly protected as a THP ether 33 followed by a three-fold Williamson etherification with phloroglucinol to afford tripodal protected alcohol 7.…”
Section: Figurementioning
confidence: 99%